Exploring the Contextual Benefits of Environmental Reporting for Corporate Sustainability in Developing Economies: A Case Study of Zimbabwe’s Mining Sector - Ncube, Thabani; Matashu, Martha (Revista Gestão & Sustentabilidade, 2026)
The paper focuses on the benefits of non-financial reporting, with an emphasis on environmental reporting in the mining companies. Thus, the purpose of this study is to investigate the context-based benefits of environmental reporting in the developing economies. This paper provide a comprehensive understanding of the contributions of environmental reporting and fosters sustainability within mining companies. A sequential exploratory research design was used to identify benefits of environmental reporting among listed mining companies in Zimbabwe. Initially, qualitative data was collected through in-depth interviews. This was followed by validation of the qualitative findings using quantitative methods. The findings show that through environmental reporting, mining companies are able to highlight their commitment to environmental stewardship, which can help to build confidence of the stakeholders. The empirical findings revealed that reporting could help companies improve the brand value, thus enhancing attractiveness of the companies to investors and various stakeholder groups. Additionally, the study established that environmental reporting in mining companies offers benefits such as enhanced transparency and accountability. It also aids in risk management by identifying and mitigating environmental risks, thereby reducing potential legal and financial liabilities. Finally, environmental reporting supports sustainability through the promotion of responsible mining, and overall, environmental reporting strengthens the reputation of the organisation and its competitive advantage in the market. In conclusion, this study revealed that understanding the benefits of environmental reporting is important for mining companies in order to foster sustainability.